Function and evolution of the prototypic CD28ζ and 4-1BBζ chimeric antigen receptors. (December 2020) - Feucht, J.; Sadelain, M.
Abstract : T cells engineered to express chimeric antigen receptors (CARs) specific for CD19 have yielded remarkable clinical outcomes in patients with refractory B-cell malignancies. The first CARs to be approved by the US Food and Drug Administration and the European Medicines Agency are CD19 CARs that comprise either CD28/CD3ζ or 4-1BB/CD3ζ dual-signalling domains. While their efficacy and safety profiles in patients with B-cell malignancies are comparable overall, the functional properties these two CAR designs impart upon engineered T cells differ significantly. Remarkably, alternative costimulatory domains have not, to date, superseded these foundational designs. Rather, recent CAR advances have focused on perfecting the original CD28- and 4-1BB-based CD19 CARs by calibrating strength of activation, pre-empting T-cell exhaustion and increasing the functional persistence of CAR T cells. This article reviews the essential biological properties of these first-in-class prototypes and their recent evolution. Highlights: CD19 chimeric antigen receptor (CAR) therapy has shown remarkable success against B-cell malignancies. The prototypic CD19 CARs comprise either CD28/CD3ζ or 4-1BB/CD3ζ signalling domains. Both CD19 CARs yield similar efficacy but impart distinct T-cell functionalities. Novel CAR designs aim to enhance the persistence or effector potency of T cells. Genome editing averts variegated CAR expression and sustains T-cell function.